TRENDS AND GROWTH RATES IN NIGERIA’S SESAME SEED PRODUCTION AND EXPORTS: IMPLICATIONS FOR AGRICULTURAL POLICY - Afolabi, Adedapo Abayomi; Roseline Boluwaji, Oloniyo; Ajewole, Oladele Charles; Akindele James, Akintola (FUDMA Journal of Sciences, 2025)
This study explored how sesame seed production and exports have evolved in Nigeria over the past five decades (1972–2022). Data were sourced from FAOSTAT, the National Bureau of Statistics, and other trade reports, and growth rates were assessed using tools such as the compound annual growth rate (CAGR) and coefficient of variation (CV). The results show that sesame production grew strongly, particularly between 2012 and 2022, when output increased by nearly 400%. Yet, this growth was unstable, affected by climate shocks, weak policies, and poor infrastructure. Exports, on the other hand, recorded a steadier rise, with an overall CAGR of 9.63%. The fastest growth came in the 1990s, when rising demand from Asia and the Middle East pushed exports up by more than 1,500%. Still, the export boom did not always match production growth. This mismatch points to deeper structural issues such as post-harvest losses, weak storage and processing capacity, and the lack of value addition. Most exports leave the country as raw seeds, which reduce potential earnings and job creation. In addition, informal cross-border trade continues to blur the true picture of Nigeria’s sesame performance. Overall, the findings confirm sesame seeds in Nigeria’s non-oil export drive but also underline the urgent need for investment in the value chain, stronger quality control, and better compliance with international standards. These steps are crucial for Nigeria to remain competitive and achieve sustainable growth in the global sesame market
Keywords: Sesame seed; Agricultural exports; Production trends; Export growth; Nigeria; Value chain